ANALYSIS OF THE IMPACT OF EARLY MARRIAGE ON ADOLESCENT REPRODUCTIVE HEALTH BASED ON HEALTH PERSPECTIVES AND ISLAMIC RELIGION - Yuana Dwi Agustin; Hosaini Hosaini; Leni Agustin (UPT Penerbitan Universitas Jember, 2020)
Background: Early marriage, which occurs, will have an impact on women's reproductive problems with the main impact that is caused by miscarriage and childbirth at risk up to the death of the mother. In islamic religion, it is forbidden for his people to do so, which is anything that gives rise to the unlawful mudlarat of the law to be carried out because it will negatively impact and risk the safety of human life. Objective: This research was conducted to investigate juvenile underage marriage perpetrators, by providing understanding and education about the risks of early marriage, researchers provide guidance and knowledge based on health sciences and islamic religious education science to the public about the negative dakpak of underage marriage, carried out continuously and continuously. Method: This research is qualitative research with descriptive method by processing the data obtained as a result that will then be interpreted systematically against the results of the research report according to the actual facts. Result: known from the data source obtained from some respondents, about the number of Teenagers who perform underage marriages. Infromasi was chosen based on the age of teenagers who were married before the age of 19 in Sumberejo Banyuputih Situbondo Village and in The Village of CurahtatalArjasaSitubondo. the factor of early marriage is that society has a history of low education, ecnomical factors, awareness, and desires of both parties, it is very influential to the vulnerability of marriage under the age of Islam responds that early marriage is not allowed if it causes mudlarat against one of the two. Conclusion: Early marriage in Sumberejo village arjasa district situbondo district is performed by women with an average age of less than 17 years, which is due to concerns if their children do not get married soon then they will have difficulty getting a soul mate in the future, the onsling of prenuptial pregnancy. follow-up, researchers are working with village governments and religious leaders to educate the public about the impact of early marriage.